EFEKTIVITAS PEMBERIAN LABU SIAM TERHADAP PENINGKATAN PRODUKSI ASI IBU NIFAS - Zasqiah, Dela Namirah (Politeknik Tiara Bunda, 2025)
Background: Exclusive breastfeeding has an important role in supporting the growth and development of babies, as well as protecting against various diseases. However, the coverage of exclusive breastfeeding in Indonesia still faces challenges. Data from the Indonesian Central Statistics Agency shows that in Banten Province, only 68.84% of babies under six months receive exclusive breastfeeding, which means that around 31.16% have not received exclusive breastfeeding. In Lebak Regency, the coverage of exclusive breastfeeding for infants aged 0-6 months in 2020 reached 70% or equivalent to 10,029 babies, a decrease compared to the previous year which reached 79.9% in 2019. Research Objectives: This study aims to evaluate the effectiveness of chayote feeding on increasing breast milk production in postpartum mothers in the Independent Practice of Midwife Okah Yulianingsih, A.Md.Keb. Research Methods: The design used was a quasi-experiment with a pretest-posttest control group design, which compared the experimental group and the control group to measure the effect of the chayote feeding intervention. Research Results: The results showed that chayote feeding significantly affected the increase in breast milk production, where 14 out of 15 respondents experienced smooth milk production after the intervention. Statistical analysis produced a p-value of 0.002 (p < 0.05). Conclusion: Based on the results of the study, the administration of chayote has a significant effect on increasing the smooth production of breast milk in the independent practice of Midwife Okah Yulianingsih, A.Md., Keb